Jayabaya’s Vision in The Javanese Cosmology: Wise Religion, Herucokro Revelation and Black Pegasus - Rohman, Saifur (Universitas Islam Negeri (UIN) Salatiga, 2022)
The paper is to find out values, world view, and norm orientation in manuscript entitled Jayabaya (without publising year) by G Rr Ay. Brotodiningrat and Primbon Pusaka Jawa Jangka Jayabaya Pranitiwakya by R Tanojo (without publising year). This study is needed because various research and publishing in the five late year have showed an interest with a history of social context, viewing, and values. Method of data collecting is close reading and method analysis is refers the phenomonelogy that stress on the concept of intensionality and extensionality. Intensionality means evidence that is showed by consciousness while extensionality refers to proof of external world. Result of this research is to prove the Javanese cosmology of harmony. It is need to live with concept harmonizing of which there are good relation with the other, environment, and the bigger cosmic in the human existence. Symbol in text of the Jangka Jayabaya, like Herucokro, Kuda Sembarni Hitam, Agama Budi, dan Hidup Harmoni, give a message of how to be a just leader, good norm, and developing a new social order.